Antibiotic Consumption and Resistance Pattern of 3 Coagulase-Negative Staphylococci Species: An Ecological Study - Herleeyana Meriyani; Dwi Arymbhi Sanjaya; Ketut Agus Adrianta (Universitas Gadjah Mada, 2021)
A group of coagulase-negative staphylococci (CoNS) was historically classified as a nonpathogenic bacteria. Over the last few decades, nosocomial infections caused by CoNS as opportunistic pathogens have increased and become one of the major nosocomial pathogens. The aim of this study was to identify the relationship between the use of an antibiotic agent for CoNS in Bali's regional public hospital and the development of antibiotic resistance during 3 years period. This study was a retrospective ecological study of antibiotic resistance and antibiotic consumption secondary data collected prospectively. It was conducted over a three years period of inpatient data. Susceptibility of CoNS to antibiotics was obtained from the hospital antibiogram of all isolates from 2017 to 2019. Sensitivity results in antibiogram were based on the standards provided by the Clinical and Laboratory Standards Institute (CLSI) with the disk diffusion method. Antibiotic consumption in DDDs/100 bed-days. The relationships between DDDs/100 bed-days of each antibiotic and rates of antibiotic resistance of each resistant strain of CoNS were tested using Spearman correlation and logistic regression. There was no significant correlation between antibiotic consumption (DDD) and the percentage of antibiotic resistance among the three CoNS species (p>0.05). However, this study found there was an inverse relationship between DDD and antibiotic resistance in Staphylococcus hominis species (OR = 0.063; CI [0.004-0.915]; p=0.043). We conclude that no significant correlation between antibiotic consumption and antibiotic resistance of the 3 CoNS species. There needs to be further research to identify antibiotic consumption, antibiotic resistance and other factors affecting antibiotic resistance.